Antimicrobial resistance in intensive care patients hospitalized with SEPSIS: a comparison between the COVID-19 pandemic and pre-pandemic era - Falasca, Katia; Vetrugno, Luigi; Borrelli, Paola; Di Nicola, Marta; Ucciferri, Claudio; Gambi, Alessandra; Bazydlo, Magdalena; Taraschi, Giorgia; Vecchiet, Jacopo; Maggiore, Salvatore Maurizio (Frontiers in Medicine, 2024)
Introduction Coronavirus disease 2019 (COVID-19) is a highly contagious viral illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It has had a dramatic effect on the world, resulting in millions of deaths worldwide and causing drastic changes in daily life. A study reported that septic complications were associated with high mortality in COVID-19 patients. This study aimed to evaluate how the COVID-19 pandemic changed the pre-pandemic and post-pandemic prevalence of sepsis in ICUs and to evaluate the different risk factors associated with mortality and the different diffusion of microorganisms and their resistance. Materials and methods We conducted a single-center retrospective observational clinical study, observing all patients in the ICU of the SS Annunziata Hospital in Chieti (Italy) who were diagnosed with sepsis and had a bacterial isolate from their blood culture. Sepsis was diagnosed by SEPSIIS III criteria. We enrolled all in-patients in the ICU from January 2018 to December 2021. We divided the patients into three groups: (1) non-pandemic period (Np) hospitalized in 2018–2019, (2) pandemic period (Pp)-COVID hospitalized in 2020–2021 with a diagnosis of COVID-19, and (3) Pp-non-COVID patients hospitalized in 2020–2021 without a diagnosis of COVID-19. Results From January 2018 to December 2021, 1,559 patients were admitted to the ICU, of which 211 patients [36 (17.1%) in 2018, 52 (24.6%) in 2019, 73 (34.6%) in 2020, and 50 (23.7%) in 2021, respectively] met the selection criteria: 88 patients in period Np, 67 patients in Pp without COVID-19, and 56 patients Pp with COVID-19. The overall mortality of these patients was high (65.9% at 30 days in Np), but decreased during the Pp (60.9%): Pp-non-COVID was 56.7% vs. Pp-COVID 66.1%, with a statistically significant association with APACHE III score (OR 1.08, 95%CI 1.04–1.12, p < 0.001), SOFA score (OR 1.12, 95%CI 1.03–1.22, p = 0.004), and age (OR 1.04, 95%CI 1.02–1.07, p < 0.0001). Between the Np vs. Pp periods, we observed an increase in a few Gram-positive bacteria such as S. capitis (1 pt. −0.9% vs. 14 pt. −7.65%- p = 0.008), S. epidermidis, Streptococcus spp., and E. faecalis, as well as a decrease in a case of blood culture positive for S. aureus, S. hominis, and E. faecium. In Gram-negative bacteria, we observed an increase in cases of Acinetobacter spp. (Np 6 pt. −5.1%- vs. Pp 20 pt. −10.9%, p = 0.082), and Serratia spp., while cases of sepsis decreased from E. faecium (Np 11 pt. −9.4%- vs. Pp 7 pt. −3.8%, p = 0.047), and Enterobacter spp., S. haemolyticus, S. maltophilia, Proteus spp., and P. aeruginosa have not changed. Finally, we found that resistance to OXA-48 (p = 0.040), ESBL (p = 0.002), carbapenems (p = 0.050), and colistin (p = 0.003) decreased with time from Np to Pp, particularly in Pp-COVID. Conclusion This study demonstrated how the COVID-19 pandemic changed the prevalence of sepsis in the ICU. It emerged that the risk factors associated with mortality were APACHE and SOFA scores, age, and, above all, the presence of ESBL-producing bacteria. Despite this, during the pandemic phase, we have observed a significant reduction in the emergence of resistant germs compared to the pre-pandemic phase.